2019
DOI: 10.3390/su11041059
|View full text |Cite
|
Sign up to set email alerts
|

The Financing Framework for Sustainable Development in Emerging Economies: The Case of Uruguay

Abstract: This paper explores the financing framework for sustainable development in Uruguay, an emerging economy, and examines whether available financing instruments contribute to achieving the sustainable development goals (SDGs) in which significant progress is still required in this country. Reports, policy documents and academic literature were reviewed to determine the types of sustainable development financing instruments available, and to analyse the challenges facing emerging economies in this regard. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…Access to finance has been identified as one of the major constraints on the sustainability of SMEs [43,44]. Gambetta et al [45] showed that the underdeveloped financial markets and weak financial instruments in emerging economies led to poor allocation of financial sources among business organizations. Access to finance is defined as the availability of financial services, in the form of demand deposits, credit, payments or insurance [46,47].…”
Section: Access To Finance and Smes' Sustainabilitymentioning
confidence: 99%
“…Access to finance has been identified as one of the major constraints on the sustainability of SMEs [43,44]. Gambetta et al [45] showed that the underdeveloped financial markets and weak financial instruments in emerging economies led to poor allocation of financial sources among business organizations. Access to finance is defined as the availability of financial services, in the form of demand deposits, credit, payments or insurance [46,47].…”
Section: Access To Finance and Smes' Sustainabilitymentioning
confidence: 99%
“…According to this mechanism, this study sets up the evaluation index to measure the coupling coordination interactions of the two subsystems. is paper firstly selects indicators for the two subsystems, respectively, based on previous studies [6,20,27,28,[44][45][46][47][48][49][50][51]. Secondly, the paper screens the data with several principles: (1) the data should represent the key components of the subsystems of the finance and the air environment; (2) indicators should be simple and easy to understand in order to reduce multicollinearity; and (3) the data can be continuously obtained [20,49].…”
Section: Coupling Coordination Mechanism and Evaluationmentioning
confidence: 99%
“…For the finance subsystem [6,27,[44][45][46][47]49], the finance scale aspect measures the actual amount of this industry, represented by the number of employees in the financial industry, total deposits and loans of the year, and the added value of this industry. e second aspect is the finance structure, which represents the performance quality of the industry, including financial correlation rate, insurance depth, financial concentrations, and loan structures.…”
Section: Coupling Coordination Mechanism and Evaluationmentioning
confidence: 99%
“…To this end, the United Nations (UN) envisions a global economic growth in harmony with nature for both individual and national prosperity towards sustainable development goals (SDGs) [11,12]. In this context, economic transformation requires innovating inclusive and productive financing policies and ensuring that such new and alternative financing models promote green and clean consumption and production behaviors within individuals, firms, organizations, societies, and governments [13][14][15][16][17]. However, a high global debt concentration retards this inclusive and productive financing and has a significant, negative impact on sustainable development [6,18].…”
Section: Sustainable Development and Global Debt Concentrationmentioning
confidence: 99%
“…Afterwards, we simplified Equation (4), which is shown in Equation (17) following Equation (15) and (16). (16) gini = numerator denominator .…”
Section: Functions Of the Environmentmentioning
confidence: 99%